Boost to learning in higher education through gamification - Rodríguez-Iglesias, Isabel; Moreno-Adalid, Ana; Gallego Trijueque, Sara (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this project is to implement a cooperative learning methodology in the university environment through a gamification strategy to promote behavioural changes in students. The stimulus tool is an innovative practice of double correction that incorporates the concept of fun. The Chi-square statistic was applied to the data obtained. In addition, students were given a questionnaire on the acquired competences to which the Mann-Whitney U test was applied. The analysis of the resultant data supports that the implemented strategy improves interpersonal skills and academic performance.